POTENCIALIDADES DO PARQUE ESTADUAL DE ITAÚNAS NO PLANEJAMENTO DE SEQUÊNCIAS DIDÁTICAS INVESTIGATIVAS PARA O ENSINO DE BIOLOGIA - Pereira, Joene Alves (2020)
Biology teaching is related to formal and non-formal education spaces, so it promotes the insertion of practices that use teaching by investigation, WHERE the student has effective protagonism. These educative spaces are relevants in the learning of sever